Do we need tailored training and development plans for European Union respiratory nurses?. Issue 2 (June 2020) - Arranz Alonso, Silvia; Christensen, Helle Marie; Díaz- Pérez, David; Narsavage, Georgia; Padilha, José Miguel; Quijano-Campos, Juan Carlos; Sajnic, Andreja; Stridsman, Caroline; Täubl, Helmut; Zakrisson, Ann-Britt; Clari, Marco
Respiratory diseases inflict a massive health burden worldwide, affecting >1 billion people. COPD, asthma, acute lower respiratory tract infections, tuberculosis and lung cancer are among the most common causes of severe illness and death globally [1]. Respiratory nurses are key members of the pulmonary healthcare team caring for people in acute settings, as well as in primary care, providing a wide range of interventions from ventilation to palliative care. Their specialised roles deliver both autonomous and prescribed interventions [2–6]. Nurses are critical players in healthcare and should be the next profession to standardise levels of education, preparing them for an active partnership with other healthcare professionals prepared to tackle the chronic disease problem in Europe https://bit.ly/3bMR76b